“PENGARUH BRAND COMMUNITY TERHADAP LOYALITAS MEREK MOBIL TOYOTA YARIS” (Deskripsi penelitian di Kota Malang) - Coniesya Mutiara Fajrina (Jurnal Ilmiah Mahasiswa FEB, 2013)
Research aims to understand and to analyze the influence of Brand Community on the loyalty to Yaris Toyota Brand in Malang City, either simultaneous or partial. Research type is explanatory research to explain causal relationship between variables through hypothesis testing.The sample of research is 50 respondents selected from official member of car community, Malang Yaris Community (MYC). Sampling technique is purposive sampling or be called also as judgment sampling. It is a random sample selection which is used based on certain consideration, which is commonly based on research goal or research problem. This test is used also to examine research instruments including validity test, reliability test, and classical assumption test. Hypothesis test is using F-test, t-test, and dominant test. Data analysis technique is using multiple linear regression analysis.Result of research indicates that based on the result of multiple linear regression analysis using F-test (simultaneous), it is concluded that simultaneously, brand community variables have influenced brand loyalty. Pursuance to result of t-test analysis, it is concluded that partially, brand community has influenced brand loyalty. Based on coefficient of regression (standardized coefficient beta),  each variable will help using the brand to have dominant influence on brand loyalty to Toyota Yaris in Malang CityKeywords: Brand Community, Brand Loyalty